Movement profiles of the balance breaking (Kuzushi) of top judoka - Möller, S.; Kittel, R.; Krüger, T.; Sprunk, S.; Rosenblum, M.; Wick, D. (World Congress of Performance Analysis of Sport VIII, 2008)
Essential aspects of an efficient Kuzushi such as an explosive force development and the maintenance of force effect over a long period of time can be tested using the two parameters GA-index and work value. It can be assumed, that the different weight classes of athletes account for the high standard deviations for the Fmax and work values. In the further process of the study, weight-class-specific reference values are to be compiled. Throwspecific characteristics of the Kuzushi are still to be analysed in terms of their final dimension in preparation for throwing techniques. In accordance with the video results and the athletes` central techniques, the movement profiles are to be created and assessed individually in connection with the special technique. This measuring instrument can also be used as a training device and - compared to non-specific strength tests - provides sport-specific information. Athletes and coaches may benefit from a description and interpretation of these parameters.